The Role of Decentralized Financial Ecosystems in Exchange Transformation in the Digital Era - Saiful Ruchiyat Cosahan; Atma Hayat; Asrid Juniar (Cita Konsultindo Research Center, 2024)
The advancement of blockchain technology has made a significant contribution to the development of the digital financial ecosystem. One of the most prominent aspects is the emergence of Decentralized Finance (DeFi) and its pivotal role in transforming exchange platforms within the digital financial ecosystem. This journal describes the primary role of DeFi in reshaping our perception of exchanges, encompassing implications for security, safety, and technological innovation Keywords : Financial Decentralization, Exchange Transformation, Digital Era